Global study of MFS superfamily transporters in arabidopsis and grapes reveals their functional diversity in plants - Patil, Sucheta S.; Prashant, Ramya; Kadoo, Narendra Y.; Upadhyay, Anuradha; Gupta, Vidya S. (Plant Gene, 2019)
The Major Facilitator Superfamily (MFS) is the largest superfamily of secondary transporters present in all organisms, from prokaryotes to higher eukaryotes, that facilitates transport of diverse molecules like sugars, vitamins, amino-acids, hormones, etc. across cell membranes. The superfamily was further expanded to MFS Superfamily (MFSS) to integrate MFS with nine more families. The present study revealed their land plant specific diversity through identification across six species from unicellular alga to higher flowering plants. We identified 71, 131, 254, 260, 213 and 203 MFSS transporters in Chlamydomonas reinhardtii, Physcomitrella patens, Selaginella moellendorffii, Oryza sativa (var. Japonica), Arabidopsis thaliana and Vitis vinifera, respectively and classified them into MFSS families and subfamilies based on their transporter classification identifiers (TCIDs). Detailed analysis of 20 land plant specific subfamilies was conducted in A. thaliana and V. vinifera. Phylogenetic and gene duplication studies revealed the expansion of sugar porter and proton dependent oligopeptide transporter families in Arabidopsis and grape. The subcellular localization of the majority of the transporters was predicted to be in the plasma membrane. Furthermore, the microarray expression analysis of MFSS transporters from Arabidopsis and grapes revealed their multi-tissue-specificity and differential regulation under biotic and abiotic stress conditions. Studies of the transmembrane topology highlighted the presence of central cytoplasmic loop along with family specific topological variations that were evident from phylogenetic analysis. Overall, this study adds to the knowledge of functional and structural diversity and evolution of MFSS transporters in plants and opens the scope for detailed physiological and functional studies on these proteins.